Microplastics: Origin, Environmental impact, Food and Beverage contamination and Management methods - Punyauppa-path, Sukrita; Punyauppa-path, Prasongsom (Asian Health, Science and Technology Reports, 2020)
Since the production of in the early 1900s to present, there have been ongoing reports on the problems of plastic and microplastic waste contaminated in the environment. Moreover, within the last 10-15 years, the number of reports on microplastics contamination and impact on living organisms have increased in almost every country around the world. This article is a review, report and analysis of the literature on microplastics and with the objectives focusing on 1) Origins and routs of microplastics contamination 2) Potential impact of microplastics on organisms 3) Microplastics in organisms, foods and beverages 4) The situation of micro-plastics in Thailand 5) The process of dealing with microplastics in the environment